2002
DOI: 10.1002/cm.10033
|View full text |Cite
|
Sign up to set email alerts
|

Transient concentration of a γ‐tubulin‐related protein with a pericentrin‐related protein in the formation of basal bodies and flagella during the differentiation of Naegleria gruberi

Abstract: The distribution of two proteins in Naegleria gruberi, N-␥TRP (Naegleria ␥-tubulin-related protein) and N-PRP (Naegleria pericentrin-related protein), was examined during the de novo formation of basal bodies and flagella that occurs during the differentiation of N. gruberi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 55 publications
3
29
2
Order By: Relevance
“…Additionally, we observed that ␥-tubulin is consistently localized to the basal bodies throughout differentiation. This result is in direct contrast to what has been previously described (32). We propose that the previous reports of Naegleria ␥-tubulin foci moving to the opposite end of the cell from the MTOC after basal body assembly were likely an artifact of using heterologous antibodies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Additionally, we observed that ␥-tubulin is consistently localized to the basal bodies throughout differentiation. This result is in direct contrast to what has been previously described (32). We propose that the previous reports of Naegleria ␥-tubulin foci moving to the opposite end of the cell from the MTOC after basal body assembly were likely an artifact of using heterologous antibodies.…”
Section: Discussioncontrasting
confidence: 99%
“…Naegleria's genome encodes two centrins: the previously characterized centrin (which we followed in this study) (19) that is a homolog of human centrin-1, and a second centrin that represents a homolog of human centrin-3 and yeast Cdc31p. Surprisingly, we did not find evidence of a homolog of pericentrin, despite a report of localization of this protein in Naegleria using heterologous antibodies (32). The presence of many known basal body genes indicates that although Naegleria's basal bodies are transient structures, they are likely canonical in composition as well as structure.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…These cells are, therefore, at beginning of differentiation when the first centrioles start to be detected by EM analysis. The initial events that occur during de novo centriole formation in Mastotermes spermatids are, therefore, very similar to the events described during the de novo formation of centrioles in HeLa cells, in which original centrioles have been removed, [La Terra et al, 2005] and during basal body assembly in Naegleria gruberi [Suh et al, 2002], where cytoplasmic foci of g-tubulin are seen before centriole appearance. As spermatid differentiation proceeds in Mastotermes the pericentrin staining concentrates near the basal region of the nucleus in correspondence of the cytoplasmic domain where centriole formation occurs.…”
Section: Discussion the Unique Multiflagellated Sperm In Insectsmentioning
confidence: 85%
“…Cell fixation and immunocytochemistry were performed as described previously (Han et al, 1997;Suh et al, 2002).…”
Section: Cell Fixation and Immunocytochemistrymentioning
confidence: 99%